2011
DOI: 10.4061/2011/670138
|View full text |Cite
|
Sign up to set email alerts
|

Role of Investigating Thrombophilic Disorders in Young Stroke

Abstract: Our knowledge about various inherited and acquired causes of thrombophilic disorders has increased significantly during the past decade. Technology for various diagnostic tests for these rare disorders has matched the rapid advances in our understanding about the thrombophilic disorders. Inherited thrombophilic disorders predispose young patients for various venous or arterial thrombotic and thromboembolic episodes. Our understanding has also improved about various gene-gene and gene-environment interactions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 76 publications
(118 reference statements)
2
13
0
6
Order By: Relevance
“…Inherited thrombophilia is associated with unprovoked venous thromboembolism (VTE) but the evidence is conflicting for arterial thrombosis, as shown in an extensive review article by Morris et al [2]. The cutoff age to define young and old is not clearly delineated, but ischemic stroke occurring in patients younger than 44 years of age is considered young [1]. Ischemic stroke secondary to an underlying hypercoagulable disorder is more common in younger patients (10-15%), but cardioembolism remains the most common etiology [1].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Inherited thrombophilia is associated with unprovoked venous thromboembolism (VTE) but the evidence is conflicting for arterial thrombosis, as shown in an extensive review article by Morris et al [2]. The cutoff age to define young and old is not clearly delineated, but ischemic stroke occurring in patients younger than 44 years of age is considered young [1]. Ischemic stroke secondary to an underlying hypercoagulable disorder is more common in younger patients (10-15%), but cardioembolism remains the most common etiology [1].…”
Section: Discussionmentioning
confidence: 99%
“…The cutoff age to define young and old is not clearly delineated, but ischemic stroke occurring in patients younger than 44 years of age is considered young [1]. Ischemic stroke secondary to an underlying hypercoagulable disorder is more common in younger patients (10-15%), but cardioembolism remains the most common etiology [1]. One study found that younger age is a predictor for ordering specialized coagulation tests [3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations